GAMBARAN PERAN ORANG TUA DALAM PENDIDIKAN SEKS REMAJA DI RT 09 DESA KEDEMANGAN WILAYAH KERJA PUSKESMAS PENYENGAT OLAK KABUPATEN MUARO JAMBI TAHUN 2013 - Aprianti Rahmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The development of technology and the environment is different than on the previous generation resulted in the development of the adolescents of today including knowledge and information on sexuality. Increasingly easy access to information to make today's teens are more likely to quickly know what the name of the relationship between the sexes or sex. The role of parents in pendidikans very necessary to reduce problem behavior sex in teens. It can be seen from didesa kedemangan teen years 213 2013 36 of them ended with the marriage of early childhoodThe research is the research Deskriftik that aims to see the description of the role of parents in the education of sex in teens in Rt 04 village Kedemangan work-area Clinics Stun Refuse Muaro Jambi Regency. Popuasi in this research are the parents who have older children in the village of Kedemangan 09 RT totalling 167 's parents while the sample research totalling 118 respondents who have children aged teens. Samples taken with the technique of simple random sampling.The results showed that out of 118 respondents 74 (62.7%) have a less Good Role in pendidikas sex and 44 (37.3%) has a good role in sex education on adolescents.Expected parents can Live his Role as best as possible and deepen their knowledge in the field of sex education, while also Granting techniques in sex education Note so that it does not cause any Haul parents and teens.Keyword : the role of parents, sex education